2019
DOI: 10.1016/j.jagp.2019.04.006
|View full text |Cite
|
Sign up to set email alerts
|

MMSE Changes During and After ECT in Late-Life Depression: A Prospective Study

Abstract: There is ongoing concern about the impact of electroconvulsive therapy (ECT) on cognition in patients with late-life depression (LLD), especially in patients for whom pretreatment Mini-Mental State Exam (MMSE) scores are low. Our aim was to examine the evolution of cognitive effects of ECT, using the MMSE in a large group of patients with LLD. Methods: One hundred nine patients aged 55 years and older with unipolar depression, referred for ECT, were included in our study. The MMSE was assessed before, during, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 42 publications
1
19
1
Order By: Relevance
“…We found that patients with psychotic symptoms had lower MoCA scores at all time points, and these patients were particularly vulnerable to cognitive side-effects early in treatment (after 1 week, T1) compared to patients without psychotic symptoms. This last finding contradicts Obbels et al (49), who found that MMSE scores increased during the whole ECT course and increased proportionally more in psychotic than in non-psychotic depressed patients. These conflicting results could be due to the more accurate measurement by the MoCA of cognitive subdomains such as delayed recall, visuoexecutive functioning and language fluency, which are commonly affected by ECT in patients with MDE (5,24).…”
Section: Discussioncontrasting
confidence: 62%
“…We found that patients with psychotic symptoms had lower MoCA scores at all time points, and these patients were particularly vulnerable to cognitive side-effects early in treatment (after 1 week, T1) compared to patients without psychotic symptoms. This last finding contradicts Obbels et al (49), who found that MMSE scores increased during the whole ECT course and increased proportionally more in psychotic than in non-psychotic depressed patients. These conflicting results could be due to the more accurate measurement by the MoCA of cognitive subdomains such as delayed recall, visuoexecutive functioning and language fluency, which are commonly affected by ECT in patients with MDE (5,24).…”
Section: Discussioncontrasting
confidence: 62%
“…Instead, the recovery of MMSE scores might reflect the relief of depression symptoms and the improvement of cognitive ability (Obbels, Verwijk, Vansteelandt, Dols, & Bouckaert, 2018; Verwijk et al., 2014). Alternatively, as some reports have pointed out, a learning effect cannot be excluded with the MMSE scale, as it is relatively simple and has been tested many times in patients (Obbels et al., 2019). We also found that the incidence of cognitive dysfunction was still higher in the propofol‐only group than in the ketamine plus propofol group throughout the treatment process, indicating that ketamine protects cognitive function, possibly due to the lower electrical dose finally used during the ECT course.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a new study reported that MMSE score increases along a course of ECT, and this showed the disconnect between MMSE score and appropriate concern about adverse cognitive effects of ECT. [ 26 ] To solve those issues, in this systematic review, all types of studies are RCTs, which creates a similar experimental condition between the 2 groups. In contrast, we used the total MMSE score for analysis in 48 h after the final ECT.…”
Section: Discussionmentioning
confidence: 99%